Plants for Sustainable Improvement of Indoor Air Quality. (June 2018) - Brilli, Federico; Fares, Silvano; Ghirardo, Andrea; de Visser, Pieter; Calatayud, Vicent; Muñoz, Amalia; Annesi-Maesano, Isabella; Sebastiani, Federico; Alivernini, Alessandro; Varriale, Vincenzo; Menghini, Flavio
Abstract : Indoor pollution poses a serious threat to human health. Plants represent a sustainable but underexploited solution to enhance indoor air quality. However, the current selection of plants suitable for indoors fails to consider the physiological processes and mechanisms involved in phytoremediation. Therefore, the capacity of plants to remove indoor air pollutants through stomatal uptake (absorption) and non-stomatal deposition (adsorption) remains largely unknown. Moreover, the effects of the indoor plant-associated microbiome still need to be fully analyzed. Here, we discuss how a combination of the enhanced phytoremediation capacity of plants together with cutting-edge air-cleaning and smart sensor technologies can improve indoor life while reducing energy consumption. Highlights: In modern energy-saving airtight constructions, the concentration of air pollutants can build up to dangerous levels, posing a serious threat to human health. Plants can efficiently remove pollutants and improve indoor air quality, although the stomatal and non-stomatal processes driving phytoremediation are poorly understood and not yet properly quantified. Indoor plants are typically selected on the basis of their aesthetic features rather than physiological requirements reflecting their capacity to remove air pollutants.